Analisis Penerapan Peraturan Pemerintah Nomor 46 Tahun 2013 terhadap Beban Pajak Wajib Pajak Orang Pribadi UMKM di Indonesia dengan Menggunakan Skema Gain/Loss - Sukaryo Sukaryo; Oktavia Oktavia (STIE Indonesia Banking School, 2016)
This study aims to determine the impact of the implementation of PP 46 Year 2013 on the tax burden of SMEs individual taxpayers, whether the tax burden becomes larger or become smaller after the implementation of PP 46 Year 2013. To answer this research question, this study using gain/loss scheme, where taxpayers who have increasing tax burden after the implementation of PP 46 Year 2013 referred to” loss” taxpayers and taxpayers who have decreasing tax burden after the implementation of PP 46 Year 2013 referred to “gain” taxpayers. Furthermore, this study also examined the impact of the implementation of PP 46 Year 2013 to the amount of tax revenue obtained from SMEs individual taxpayers, which is confirmed the presumptive tax regime under the rule. The results of this study show that: (i) Implementation of PP 46 Year 2013 led to the tax burden of SMEs individual taxpayers becomes higher. Of the 1783 samples (SMEs individual taxpayers), there were 1247 sample have experienced loss. It was concluded that PP 46 Year 2013 led to a higher tax burden for SMES individual taxpayers; and (ii) PP 46 Year 2013 have contributed in increasing tax revenues and the number of SMEs taxpayers who pay taxes, but it is not significant.